2019
DOI: 10.1029/2019gl085090
|View full text |Cite
|
Sign up to set email alerts
|

A Definition of Rapid Weakening for Tropical Cyclones Over the Western North Pacific

Abstract: The statistical characteristics of rapid weakening (RW) tropical cyclones over the western North Pacific are explored from 1988 to 2017. The RW is defined as approximately the 95th percentile of all 24-hr over-water weakening rates, corresponding to a 40 kt (20.6 m/s) or greater decrease in the maximum surface wind over a 24-hr period. Statistical analysis suggests that RW tropical cyclones tend to possess higher intensities and faster translation than non-RW tropical cyclones. Relative to the non-RW cases, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 35 publications
(59 reference statements)
3
34
0
Order By: Relevance
“…Ma et al. (2019) found almost constant 24 hr weakening rate above an initial intensity of Category 3 or higher. Their definition of weakening includes fluctuations above CAT 3 (e.g., from CAT 4 to 3 within 24 hr) and is thus different, as it does not consider the final decay to CAT 1 as we explicitly consider here.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ma et al. (2019) found almost constant 24 hr weakening rate above an initial intensity of Category 3 or higher. Their definition of weakening includes fluctuations above CAT 3 (e.g., from CAT 4 to 3 within 24 hr) and is thus different, as it does not consider the final decay to CAT 1 as we explicitly consider here.…”
Section: Discussionmentioning
confidence: 94%
“…The weakening stage following the LMI has received much less attention (Colomb et al., 2019; Ma et al., 2019; Wood & Ritchie, 2015). This is somewhat surprising and anomalous since the weakening phase lasts for a similar length of time as intensification and is also more likely to occur close to land than over the open ocean and thus is important to understanding impact.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, prior research has shown that RW events typically occur when TCs entrain dry air (Wood & Ritchie, 2015) or encounter increased VWS (Ma et al, 2019). However, there are slight increases in 700‐ to 500‐hPa RH and slight decreases in 850‐ to 200‐hPa VWS over the significant region from 1982–2000 to 2001–2019 (Figures 4c and 4d).…”
Section: Spatial Changesmentioning
confidence: 91%
“…There are also significant increasing trends for all four data sets for the period of 1982–2019, indicating consistency among the different best tracks. Several prior studies have used the JTWC data set to investigate TC characteristics related to RW over the WNP (Liang et al, 2018; Ma et al, 2019). Given the similar interannual trends between all four TC data sets as well as the historical precedence for using JTWC, we choose to use JTWC data in this study as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation